Spatiotemporal evolutionary patterns of the hydrochemistry of Jurassic conglomerate aquifers under the influence of curtain walls - Luwang CHEN; Minghui WU; Xiaowei HOU; Yongsheng HU; Miao ZHANG; Xinyue CAI; Xiaoxi YIN; Xiaoping SHI (Meitian dizhi yu kantan)
ObjectiveCurtain walls, recognized as a primary project for the prevention and control of water disasters in coal mines, will change the dynamic field of groundwater. Furthermore, their dissolution will affect the chemical field of groundwater, leading to variations in its hydrochemical composition. MethodsThis study investigated the Jurassic conglomerate aquifers in the Zhuxianzhuang Coal Mine, Huaibei coal field. Based on the statistics of conventional hydrochemical composition, Piper diagrams, ion combination proportions, and principal component analysis (PCA), this study explored the impacts of curtain walls on the hydrochemistry of the aquifers and determined the spatiotemporal hydrochemical evolutionary patterns under the influence of the curtain walls. Results and Conclusions The results indicate that the hydrochemical characteristics differ greatly between inside and outside the curtain walls, with the groundwater inside the curtain walls exhibiting elevated Ca2+ and Mg2+ concentrations compared to that outside the curtain walls. After the construction of the curtain walls, the hydrochemical processes are dominated by the dissolution of the curtain walls based on the leaching and dissolution of calcite (CaCO3) and dolomite (CaMg(CO3)2), accompanied by varying degrees of pyrite oxidation, alternating adsorption of cations, and desulfurization. Influenced by mining, the dissolution of the curtain walls produces significantly enhanced impacts on groundwater within them, with the dissolution of the northern curtain wall relatively weaker than that of the eastern counterpart. The results of this study will provide theoretical support for the monitoring and protection of curtain walls and the environmental protection of groundwater.